Use of New Oral Anticoagulants in the Treatment of Venous Thromboembolism and Thrombotic Prophylaxis - Akin, Muharrem; Schäfer, Andreas; Akin, Ibrahim; Widder, Julian; Brehm, Michael (Cardiovascular & Haematological Disorders - Drug Targets, 2015)
Thrombo-embolism of the venous system consisting of deep vein thrombosis (DVT) and pulmonary embolism (PE) is common and associated with high morbidity and mortality. Symptomatic venous thrombembolism (VTE) manifests in about 1/3 of cases as PE and 2/3 as DVT. There is a strongly compound between early mortality after venous VTE and PE, age, malignancies and cardiovascular diseases. Anticoagulation therapy is the main therapeutic approach for the treatment of acute VTE and to prevent recurrent VTE events. For decade’s classic anticoagulants like heparin, low-molecular-weight heparins (LMWHs), fondaparinux, and vitamin K antagonists have been the gold standards in therapy and are widely used. Novel oral anticoagulants (NOAC) like the direct thrombin inhibitor (dabigatran etexilate) and the direct factor Xa inhibitors (e.g. rivaroxaban, apixaban, and edoxaban) have been introduced to overcome the drawbacks of vitamin K antagonists. The efficacy and safety of these NOAC have been investigated in several randomized trials. Here we want to give an overview about the NOACS in the treatment of acute and chronic VTE and their use for primary prevention of acute VTE.
Keywords: warfarin